Demand for Reserves and the Central Bank's Management of Interest Rates - Sébastien Kraenzlin; Martin Schlegel (Swiss Journal of Economics and Statistics, 2012)
The implementation of monetary policy is prevalently done by interest rate targeting with a short term market rate serving as operational target. The instruments for achieving the operational target are the provision of reserves and the interest rate charged in these transactions. This paper presents a model for the estimation of the demand curve for reserves, derived from the central bank's fixed rate tender auction and the interbank money market. Using data from Switzerland, the slope of the demand curve is estimated. Furthermore, properties of the demand curve such as the slope patterns in the course of a maintenance period and the slope in different monetary regimes are assessed. We find a steeper demand curve towards the end of the maintenance period and an increasing slope when the general interest rate level is high. Further, we investigate the role of the Swiss National Bank's (SNB) interest rate in the fixed rate tender auctions. There is evidence that the SNB uses its auction rate to guide the interbank market rate.
Keywords: D40; E41; E43; E52; 330; Implementation of monetary policy; money demand; fixed rate tender auction; repo; Switzerland